Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter Andreas; Hu, Chunling; Hart, Steven N.; Ruebner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Huebner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17-0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of ~5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.